2023
DOI: 10.1093/mnras/stad1957
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic simulations of the disc of gas around supermassive black holes (HDGAS) – I. Molecular gas dynamics

Abstract: We present hydrodynamic simulations of the interstellar medium (ISM) within the circumnuclear disk (CND) of a typical AGN-dominated galaxy influenced by mechanical feedback from an active galactic nucleus (AGN). The simulations are coupled with the CHIMES non-equilibrium chemistry network to treat the radiative-cooling and AGN-heating. A focus is placed on the central 100 pc scale where AGN outflows are coupled to the ISM and constrained by observational Seyfert-2 galaxies. AGN-feedback models are implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Misalignment between ionized gas and stellar kinematic angles is more prevalent in galaxies with a higher fraction of active black holes. Studies have also demonstrated the stable misalignment of gas discs after mergers [33] and the influence of mechanical AGN feedback [37] on the gas misalignment. To further advance our understanding, future research should focus on exploring the sources and dynamics of gas accretion in BGGs, particularly the roles of hot and cold accretion processes and the influence of active galactic nuclei (AGN).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Misalignment between ionized gas and stellar kinematic angles is more prevalent in galaxies with a higher fraction of active black holes. Studies have also demonstrated the stable misalignment of gas discs after mergers [33] and the influence of mechanical AGN feedback [37] on the gas misalignment. To further advance our understanding, future research should focus on exploring the sources and dynamics of gas accretion in BGGs, particularly the roles of hot and cold accretion processes and the influence of active galactic nuclei (AGN).…”
Section: Discussionmentioning
confidence: 98%
“…These combined factors give rise to a multifaceted and dynamic system. The ISM gas within the circumnuclear disk (CND) of an AGN-dominated galaxy, particularly a Seyfert-2 type galaxy like NGC 1068 5 , was extensively investigated through hydrodynamic simulations referred to as HDGAS 6 [37]. The study utilized these simulations to explore the properties and dynamics of the gas in the CND influenced by mechanical AGN feedback.…”
Section: Gas Misalignment In Agn-dominated Galaxies: Insights From Hy...mentioning
confidence: 99%
See 2 more Smart Citations
“…As the transition approaches, this mixing becomes less complete and the situation begins to resemble the large-scale, cooled (i.e., momentum-conserving) shocks considered by Fabian (1999). Substantial mass loading in the outflow-driven shock, whether disk-wind-driven (Raouf et al 2023) or radio-jet-driven (Venturi et al 2023), sets favorable conditions for postshock cooling. The cooling column can be accumulated by some combination of shock compression and turbulent mixing (Begelman & Fabian 1990) facilitated by Rayleigh-Taylor and Kelvin-Helmholtz instabilities.…”
Section: Transitionmentioning
confidence: 99%